خصائص مسانيد النساء من خلال المعجم الصغير للطبراني - الحسبان، خلود محمد سويلم Alhosban, Kholoud Mohammed Sweilam (جامعة آل البيت, 2018)
تهدف هذه الدراسة إلى جمع مسانيد النساء من أحاديث "المعجم الصغير" للطبراني، ثم دراستها؛ لتظهر الخصائص العامة لرواية الصحابيات من حيث عدد مسانيدهن، وقلة روايتهن، وكثرة رواية عائشة أم المؤمنين، وتنوع صور الرواية عنها، وصور الرواية عند غيرها من الصحابيات، وتبين محتوى رواياتهن، وطرق الرواية عنهن وأنها كلها كانت بالسماع، وأنواع من روى عنهن من النساء والرجال وصلة الرواة عنهن بهن، وأن غالب أحاديثهن كان محتواه فيما يتصل بشؤون المرأة... وغير ذلك مما يؤكد على خدمة المرأة للحديث الشريف، وينبه على جهودها في الرواية والتبليغ.
This research aims to collect women masanids from "Al-mu'jam Al-sageer" for Attabarani, and then stading it to show the common aspects for sahabiat's narration in terms of their masanid's numbers, small amount of theirs narrations, a lot of Aysha (believers mother) narrations and diversity of here narrations, and sahabiat's narration ways to show their narration content and what was the transformation ways narrate their stories (most of these ways have been done by listening) and who narrated their stories from men and women and what was the relation between them. keep in your mind that most of their narration's content has been related to the women affairs which indicates the importance of women services for hadith sharif and to show her efforts in telling and narration.
Keywords: الأحاديث النبوي -- الجرح والتعديل -- الحديث المسند -- كتاب المعجم الصغير -- الطبراني، سليمان بن أحمد بن أيوب، ت. 360 هـ